PENGANTAR LATAR BELAKANG KITAB KISAH PARA RASUL (INTRODUCTION TO ACTS BACKGROUND) - Bobby Kurnia Putrawan (QUAERENS: Journal of Theology and Christianity Studies, 2019)
The Book of Acts is an important book in building Christian theology. Biblical experts debate the background to the existence of the book of Acts. Where some biblical experts put this book in an unfavorable position and some maintain in a good position. This article discusses the background of the book of Acts from an evangelical perspective which includes the name of the book, author and year of writing, Sources Used by Luke, the purpose and contents of the book. The result of this writing is that this book was written by Luke around 63 CE and is believed to have the authority of God's word to teach Christians. Kitab Kisah Para Rasul merupakan kitab yang penting dalam membangun teologi Kristen. Para ahli biblika memperdebatkan latar belakang keberadaan kitab Kisah Para Rasul. Dimana sebagian para ahli biblika menempatkan kitab ini pada posisi yang kurang baik dan sebagian mempertahankan dengan posisi yang baik. Artikel ini membahas latar belakang kitab Kisah Para Rasul dari perspektif injili yang mencakup nama kitab, penulis dan tahun penulisan, Sumber-Sumber Yang Dipergunakan Lukas, tujuan dan isi kitab. Hasil penulisan adalah kitab ini ditulis oleh Lukas sekitar tahun 63 M dan dipercayai memiliki otoritas firman Tuhan untuk mengajar umat Kristen.